Increases in intracellular water explain strength and power improvements over a season - Silva, A. M.; Matias, C. N.; Santos, D. A.; Rocha, P. M.; Minderico, C. S.; Sardinha, L. B. (International Journal of Sports Medicine, 2014)
Changes in body components occur over a season, but their impact on performance is still unclear. We aimed to analyze the relationship between changes in leg strength and jump performance with body composition over a season in highly trained athletes. Measures from the beginning to the main competitive periods of a season were obtained in 40 male and 23 female basketball, handball and volleyball players (20±5 years) for fat (FM) and fat-free mass (FFM) estimated by DXA. Total body water (TBW) and extracellular water (ECW) were assessed by deuterium and bromide dilution, respectively, and intracellular water (ICW) was calculated as TBW minus ECW. Maximal strength was determined by the leg press, while jumping height was assessed with squat (SJ) and countermovement (CMJ) jumps. Significant improvements in strength (12.5±20.8%) and jumping height (SJ:8.3±13.9%; CMJ:6.3±8.5%) were found. FFM, TBW and ECW significantly increased (3.0±2.7%; 1.7±5.5%; 3.0±8.6%, respectively), while %FM decreased (-4.5±9.1%) and no changes were observed in ICW (1.2±9.7%). Among body composition changes only ICW was associated with performance even adjusted for gender, age, season length and sport (strength: Beta71.209, p=0.012; SJ: Beta=0.311, p=0.049; CMJ: Beta=0.366, p=0.018). Body composition, strength and jumping height improved over a season and ICW was the main predictor of performance in national level players.